Andrew Viterbi's fabulous formula [Medal of Honor]. - Perry, T.S (IEEE spectrum)
This paper presents the story of an unusually bright and hard working professor who wanted to explain a difficult concept in clear and simple terms in order to better teach his students. Viterbi working from Jet Propulsion Laboratory helped developed phase-lock loop. Viterbi also started consulting on applications of his algorithms and called their firm Linkabit. The company worked on various defense and commercial satellite modems and terminals. It also built a satellite signal scrambler called Videocipher for the cable channel HBO. Years later OmniNet was founded, envisioned mobile satellite network and hired Qualcomm to build it. Qualcomm's solution was to use spread-spectrum communications and used the Viterbi algorithm to help extract the original signal from the noise. With the launch of OmniTracs, which is a trucking systems, scrappy start-up took on the mobile phone industry. Viterbi and his colleagues also figured out a way to have each handset and tower analyze the quality of its own signals as well as the other conversations being transmitted around it; the tower would then adjust power usage until the handset was transmitting just enough signal to work. One of Viterbi's earliest investments was in VoiceSignal Technologies, which used the Viterbi algorithm for voice recognition systems in cellphones, including the iPhone.